2018
DOI: 10.1016/j.seares.2018.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Underwater video offers new insights into community structure in the Grande Vasière (Bay of Biscay)

Abstract: Based on towed underwater videos, diversity patterns and their main environmental and anthropogenic drivers were assessed in the "Grande Vasière" (northeast Bay of Biscay), one of the main French fishing grounds. The density of bentho-demersal megafauna was recorded along 152 transects in this area in 2014. The highest number of taxa and densities were observed on the external margin of the Grande Vasière, in deep areas with low fishing intensity. The highest levels of taxa evenness were located on the central… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
(61 reference statements)
1
2
0
Order By: Relevance
“…All these taxa are dominant in the GV, as they represent 49% of the whole estimated biomass of bentho-demersal species. Consistent with our results, Meŕillet et al (2018b) observed that scavenger species feeding on benthic organisms damaged by bottom trawling are more frequent in the Northern muddy areas of the GV. In 2008, Hily et al showed a decline of endofauna diversity between 1966 and 2001 in the North and center of the GV which they explained by a sediment homogenization, shifting from mud to sandy mud substrata, related to high bottom trawling intensity and terrigenous inputs due to onland anthropogenic activities.…”
Section: Drivers Of Ep Bundlessupporting
confidence: 92%
See 1 more Smart Citation
“…All these taxa are dominant in the GV, as they represent 49% of the whole estimated biomass of bentho-demersal species. Consistent with our results, Meŕillet et al (2018b) observed that scavenger species feeding on benthic organisms damaged by bottom trawling are more frequent in the Northern muddy areas of the GV. In 2008, Hily et al showed a decline of endofauna diversity between 1966 and 2001 in the North and center of the GV which they explained by a sediment homogenization, shifting from mud to sandy mud substrata, related to high bottom trawling intensity and terrigenous inputs due to onland anthropogenic activities.…”
Section: Drivers Of Ep Bundlessupporting
confidence: 92%
“…Available video footages from 2014 to 2018 were reanalyzed to identify all organisms visible. Video of the seabed are watched during 7 minutes and each species between two lasers (spaced 0.75 meters apart) is counted and identified at the lowest taxonomic level by visual inspection (Meŕillet et al, 2018b). EVHOE, part of the International Bottom Trawl Survey, targets the demersal species between October and November in the Bay of Biscay and the Celtic Sea since 1997 (Laffargue et al, 2021).…”
Section: The Grande Vasière and Its Benthodemersal Biodiversitymentioning
confidence: 99%
“…Certainly, scientific trawl surveys are much less destructive than commercial operations and are useful to collect biological samples for diet and ageing studies, allowing the estimation of population age structures, the calculation of growth and mortality rates, which are essential for the management and monitoring of fish populations (McIntyre et al, 2015). However, despite the higher efficiency of bottom trawls, our study has shown that videos may be an important addition to bottom trawl methods, recording elusive species and also detecting impacts, complementing previous studies showing that video is an appropriate method for studies aiming at analyzing the distribution of fish or community structure (Assis et al, 2007;Stoner et al, 2007;Schaner et al, 2009;Mérillet et al, 2018).…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 67%
“…Hardly anything is known on the biology and habitat of this species, because it is very scarce in samplings performed on bottoms affected by the trawl fishery (Abelló et al 1988(Abelló et al , 2002, which almost specifically targets soft, sandy and/or muddy bottoms. This species is usually reported from continental shelf rocky areas or close to rocky outcrops, where it has been identified in pictures and videos using remote operated vehicles (Mérillet et al 2018).…”
Section: Discussionmentioning
confidence: 99%